2013
DOI: 10.1185/03007995.2013.821056
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of medication adherence in patients with type 2 diabetes mellitus

Abstract: Identified risk factors can guide medical professionals in their attempts to increase the likelihood of patient adherence to drug treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
103
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 32 publications
15
103
4
2
Order By: Relevance
“…In this study, a visit by a patient to the endocrinologist because of vague complaints of an undiagnosed cancer might be a competing event [28]. Moreover, missing dispensing data (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a visit by a patient to the endocrinologist because of vague complaints of an undiagnosed cancer might be a competing event [28]. Moreover, missing dispensing data (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this study adherence was measured using data for prescriptions dispensed and since it was not known whether patients actually took the medications, hence the authors considered that adherence may have been overestimated. 6 In another study adherence to medication was measured by using the Medication Compliance Questionnaire and approximately 53% of patients in the study population were found to be nonadherent. 7 One of the major reasons for such variable rates of nonadherence reported in different studies is that there is no standard, universally accepted definition of adherence due to which patients may report adherence according to their own personal definitions rather than conventional medical concepts of non-adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman correlation test was used to find correlation between adherence and age, gender, number of medicines, number of coexisting illnesses. Graph pad prism software version 6.01 was used to analyze data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with DM are more prone to indulge in non adherence and studies report that these patients have the lowest adherence to their medication regimen. 8 It is so because pharmacotherapy of DM includes challenging tasks such as remembering the medications, their frequency of administration and use of many drugs pose a challenge. Studies conducted on the subject indentify these issues as major barriers to compliance.…”
Section: Introductionmentioning
confidence: 99%